New Cheilostomata (Bryozoa) species from sublittoral and bathyal zones off the Faroe Islands, with some comments on allied taxa - Denisenko, Nina V. (Zootaxa, 2018)
Two new species of cheilostome Bryozoa are described from the Faroe Islands archipelago. Cinclidia aculeata n. gen. et sp. is a new cribrilinid taxon, distinguished from other cribrimorphs by the skeletal characters of the frontal shield and ooecium, and the absence of avicularia. A second new species, Turbicellepora faroensis n. sp., is distinguished by the shape of the orificial sinus, peristome, and suboral and interzooidal avicularia as well as by the presence of distolateral, tube-shaped adventitious avicularia (paired or single). Examination of new material of congeneric species supports the validity of the new taxon and further clarifies the separate status of Turbicellepora tuberosa (Smitt, 1868) sensu Hansen (1962) and T. hansenae Denisenko, 2016.